PERSEPSI MASYARAKAT TERHADAP SISTEM PEGADAIAN SYARIAH (Studi Kasus Di Pegadaian Syariah Idi Rayeuk) - febi febi; Iskandar Budiman; Fakhrizal Fakhrizal; Munawwarah Munawwarah (JIM: Jurnal Ilmiah Mahasiswa, 2019)
The financial instution is delived into, namely bank financial instutions and non-bank financial instutions. One of the non-bank financial instutions is instution in the form of public company (perum). The background of this research is to know the views and perceptions of the society to the pawnshops of sharia branch of idi rayeuk as well as the factors that determine the community to choose pawnshops as one source to abtain funds. The problem in this research is how is the society perception of sharia pawn system in idi rayeuk and to know what are the factors that determine the people prefer anh how sharia pawnshops in running the system and whether people understand about how the system implemented by pawnshop sharia. In this research descriptive in the form of field research Descriptive method is a method in examining the status of a group of people, an object, a condition, a system of thought or an event in the present. The purpose of this descriptive research of sharia pawn system. The results of research that has been done shows that the community is very supportive of sharia pawnshops, with sharia pawnshops can help the community down in obtaining funds quickly easil, greatly assist the community in its financial problems to meet their needs but the lack of socialization conducted by pawnshops sharia making people who pawned gold or other goods made ignorance and lack of understanding of the system and akad used by sharia pawnshops, this resulted in 100% of respondents experiencing a lack of understanding of the system, products and contracts implemented by the sharia pawnshops.